PERANAN ORANG TUA MENDAMPINGI BELAJAR ANAK DIRUMAH ERA PANDEMIC COVID 19 KELAS VII SMP NEGERI 19 PONTIANAK - Hasanah, Nur; Asrori, Muhammad; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
During the Covid-19 pandemic in Class VII SMP Negeri 19 Pontianak, the purpose of this study is to describe the role parents played in allowing their children to study at home. This study employs a quantitative descriptive approach. Data was gathered using methods other than tests, like questionnaires. There were 210 people in the study's population, and up to 63 people were sampled. The showed that during the COVID-19 pandemic Class VII SMP Negeri 19 Pontianak, parents played a "good" role in helping their children study at home. In the category of "enough," parents played a role in providing learning resources at home for 59,87 percent of children. The job of guardians in giving inspiration to learn at home 67,33% is in the "upside" classification. The percentage of parents who supervise their children while they are studying at home reaches 67,14 percent, which includes the percentage of parents who help students overcome learning obstacles and is rated "good." Based on this description, it is possible to draw the conclusion that parents' participation in helping their children study at home during the Covid-19 pandemic at Class VII SMP Negeri 19 Pontianak is typically rated as "good." This indicates that parents of Class VII SMP Negeri 19 Pontianak students participate in helping their children study at home in a satisfactory manner. BK teachers should be expected to be able to visit students with learning difficulties at home, according to suggestions. in addition to actively contacting the parents of seventh-grade students to support their children's learning.